A Study of Edward Bond’s Concept of Rational Theatre and its Role in Contemporary Political Drama - Sibgatulah Nazki; Imtiyaz Ahmad Bhat (International Journal of Global Sustainable Research, 2024)
This study examines Edward Bond’s concept of Rational Theatre. It focuses on how his plays give a critical response to violence, injustice, and social systems. The purpose is to analyze Bond’s theory and see how it shapes both his plays and his wider ideas about theatre as a tool for social change. Edward Bond became an important playwright in post-war Britain. He challenged traditional theatre by bringing political ideas onto the stage. Bond worked during a time of state violence, capitalism, and moral decline. In response, he created the idea of Rational Theatre. This is theatre that uses reason and critical thought to reveal social problems and encourage audiences to reflect. His plays, such as Saved (1965) and Lear (1971), sparked debates about censorship, stage violence, and the political role of theatre. This research uses a qualitative method, studying Bond’s plays closely. It also reviews his essays and interviews. The study uses performance theory and political criticism to see how Bond creates Rational Theatre. It looks at his use of staging, language, character, and themes. The analysis shows that Rational Theatre uses strong images of violence, isolation, and social collapse. These force the audience to think deeply and respond morally. Bond’s plays do not allow passive viewing. Instead, they make people face the real causes of cruelty and injustice. Bond’s work shows that theatre can be a rational, public space for ethical thinking. His plays link personal suffering with larger social and political problems. He uses theatre to build critical awareness. In this way, Rational Theatre is not propaganda. It is a shared process of reasoning and reflection. Edward Bond’s Rational Theatre changes how we see drama today. It says theatre must help society question itself and imagine solutions. The study ends by saying Bond’s work is still important today. His ideas guide theatre makers who want to combine artistic form with political purpose, especially in times of social crisis